Cryoseston of the Pirin Mountains, Bulgaria - Cepak, Vladislav; Lukavsky, Jaromir (Acta Botanica Croatica, 2013)
In the cryoseston community of the Pirin Mountains, 18 species were determined. Chlorophyta: Chlamydomonas nivalis (predominant), Chloromonas brevispina,Chloromonas rostafinski, Chlainomonas rubra (new genus and species for Bulgaria, documented in Europe for only the second time), Cystococcus nivicolus and Stichococcus nivalis. Bacillariophyceae: Aulacoseira granulata var. angustissima, Hantzchia amphioxys, cf. Surirella. Fungi: cf. Chytridium chlamydococcii. Deuteromycetes: Selenotila nivalis, Chionaster nivalis, and saprophytic fungae cf. Myzocytium, Rhodosporidium toruloides, Alternaria sp. and cf. Cladosporium, in pollen grains. Bacteria: Leptothrixochracea. Ciliata: Vorticella campanula. The composition of cryoseston in the Pirin Mountains is characteristic for high mountains where Chlamydomonas nivalis predominates.